2002
DOI: 10.1053/jhep.2002.33334
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of canrenone in patients with preascitic cirrhosis

Abstract: In patients with cirrhosis and portal hypertension, standing induces a reduction in cardiac index (CI) and an increase in systemic vascular resistance index. Our previous studies indicate that this abnormal hemodynamic response to standing is due to an altered myocardial function, because cirrhotic patients are unable to compensate for the reduced preload with an increase in left ventricular (LV) ejection fraction (EF) and stroke volume. To evaluate whether the cardiac dysfunction in cirrhosis is influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
1
13
0
3
Order By: Relevance
“…However, although there is no clear evidence on the role of [pH] i in the regulation of ECM protein synthesis, it is well established that any derangement in the organization of the actin-containing cytoskeleton has implications for the regulation of ECM synthesis. 59,60 Finally, the observation that canrenone may reduce the contractility of activated HSC in response to a strong vasoconstrictor such as thrombin supports the hypothesis, derived from several clinical and experimental studies, [2][3][4][5] that antialdosteronic drugs may directly exert beneficial effects on portal pressure.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, although there is no clear evidence on the role of [pH] i in the regulation of ECM protein synthesis, it is well established that any derangement in the organization of the actin-containing cytoskeleton has implications for the regulation of ECM synthesis. 59,60 Finally, the observation that canrenone may reduce the contractility of activated HSC in response to a strong vasoconstrictor such as thrombin supports the hypothesis, derived from several clinical and experimental studies, [2][3][4][5] that antialdosteronic drugs may directly exert beneficial effects on portal pressure.…”
Section: Discussionsupporting
confidence: 60%
“…Because the effects of antialdosteronic drugs on portal pressure have been shown in several clinical and experimental studies, [2][3][4][5] we then explored whether canrenone is able to reduce thrombin-induced intracellular calcium increase and cell contraction in activated human HSC. As previously reported, 26 stimulation of human HSC with thrombin resulted in increased [Ca 2ϩ ] i coupled with a transient reduction of cell area, indicating reversible cell contraction.…”
Section: Effect Of Canrenone On Thrombin-induced Intracellular Calciumentioning
confidence: 99%
See 1 more Smart Citation
“…As far as diastolic dysfunction is concerned, many etiological factors have been reliably advocated as potential pathogenic agents: notably substances as NO [18][19][20][21], TNF [22], reactive nitrogen species [23], neurohormones [24][25][26][27][28] may well affect heart structure and function along with circulatory overload [24,29] and overactivity of the SNS [30]. Thickening of heart parietal walls has been reported [12,14,17,31], nevertheless the nature of the structural changes underlying diastolic dysfunction has not been clarified so far. Available literature data are based on animal models [32][33][34] and on autoptic findings [35] overall handling conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on defects in the SNS, but several papers have emphasized the importance of vagal impairment for sodium and fluid retention [68,70]. Blood pressure responses to orthostasis are impaired, probably because of a blunted baroreflex function [71,72] and the cardiovascular responses to pharmacological stimulations with angiotensin II, noradrenaline and vasopressin are abnormal [73,74]. Captopril may, to some extent, correct vagal dysfunction in cirrhosis [68] and neuromodulation by the RAAS is also supported by data from Laffi et al, who recently reported that canrenone, an aldosterone antagonist, normalized cardiac responses to postural changes in compensated cirrhotic patients [72].…”
Section: Correction Of Circulatory Dysfunctionmentioning
confidence: 99%